A molecular genetic perspective on the evolution of Hyalomma ticks with emphasis on the phylogeography of H. truncatum - Sands, Arthur Francis (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.